Comparison between Primary Repair Versus Loop ileostomy in ileal Perforation (Medical Forum Monthly, 2020)
Objective: Objective: to compare the outcomes primary repair and loop ileostomy in ileal perforated patients.Study Design: Randomized controlled trial study.Place and Duration of Study: This study was conducted at the General Surgery department of Bakhtawar Amin Medical and Dental College, Multan and Ghazi Medical College Dera Ghazi Khan. Study was completed in one-year duration from January 2019 to January 2020.Materials and Methods: Fifty proven patients of ileal perforation were enrolled in study and divided into two (group A, B) groups by lottery method. Group A managed with primary repair and B with loop ileostomy. SPSS version 23 was used for data analysis.Results: Clinical presentations such as pain abdomen, vomiting, fever, constipation, abdomen distension and trauma of Group A was noted as n=5 (20%), n=6 (24%), n=4 (16%), n=3 (12%), n=5 (20%) and n=2 (8%), respectively. While, clinical presentations such as pain abdomen, vomiting, fever, obstruction, abdomen distension and trauma of Group B was noted as n=4 (16%), n=4 (16%), n=8 (32%), n=2 (8%), n=4 (16%) and n=3 (12%), respectively. The difference was statistically insignificant.Conclusion: Loop ileostomy is a better choice in management of ileal perforation as compare to primary repair. It is associated with less postoperative complications and this also helpful in reducing mortality in perforated cases.